Studying microbiology with Glenn F. Webb - Martin J. Blaser (Mathematical Biosciences and Engineering)
I began working with Glenn F. Webb in 1997.At that time, I was on the faculty of Vanderbilt University,in the School of Medicine, in the Department of Medicine,in its Division of Infectious Diseases.As with mathematics, modern medicine has its different disciplines(e.g. Surgery and Internal Medicine), and then further subdivisions(e.g. Cardiology and Infectious Diseases).Within Internal Medicine, most of the divisions are based on thetreatment of conditions that relate to a single organ or group oforgans -- the heart, the lungs, the kidneys, the digestive system.But the discipline of Infectious Diseases was based on a different concept:the war between humans and microbes.For more information please click the “Full Text” above.